Comparative Estimation of the Results Bus Body Section Computer Simulation and Experimental Data - Rogov, P. S.; Orlov, L. N.; Vashurin, A. S.; Tumasov, A. V. (Acta Technica Jaurinensis, 2014)
This paper deals with a rollover computer simulation (according to ECE R66 Regulation) of the bus section, which is performed on the base of a light commercial vehicle. It gives an overview of the used simulation approaches. Comparison between the calculative and experimental data is implemented on the base of one of the specified methods. It considers in details the bus rotation process, which occurs before its impact with ground. The results of the analysis allow us to make a conclusion about the bus rotation influence on the bus body deformation.